Dam hydraulics - Vischer, D. (Wiley, 1998)
This book develops the main themes of water flow in dam structures, emphasizing the hydraulic principles governing the design, construction and refurbishment of dams. Opening with an overview of the various dam structures, it then develops fundamental topics including: reservoir sedimentation, waves due to landslides and dambreak waves. The authors provide a systematic analysis of the various phenomena associated with dam hydraulics, illustrated with appropriate figures and photographs of laboratory models and prototype structures.